Bioactivities and botanical origin differentiation of malaysian stingless bee honey produced by heterotrigona itama and geniotrigona thoracica - Ng, Wen Jie (2022)
Stingless bee honey is generally valued for its distinguished flavor and health benefits but scientific studies about the differentiation of stingless bee honey based on honeydew and blossom origins are very limited. Such differentiation is crucial for the authenticity of stingless bee honey. In this study, 23 raw stingless bee honey samples produced by Heterotrigona itama and Geniotrigona thoracica were analysed. 13C NMR spectroscopy was employed to quantify the seven major sugar tautomers in stingless bee honey samples, the major sugar compositions of honeydew and blossom types were found not to be significantly different. Although physicochemical parameters including moisture content, free acidity, electrical conductivity, ash content, acetic acid, diastase, hydrogen peroxide and mineral elements levels of honeydew honey were found to be significantly higher; total soluble solid, proline and hydroxymethylfurfural were significantly lower than blossom honey. Greater antioxidant capacity in honeydew honey was proven with higher total phenolic compounds, ABTS, DPPH, superoxide radical scavenging activities, peroxy-radical inhibition, iron chelation and ferric reducing power. Principal component analysis (PCA) revealed that differentiation between honeydew and blossom origin of stingless bee honey is possible with certain physicochemical iv and antioxidant parameters. Chemometrics are suggested to be useful to determine the authenticity and botanical origin of stingless bee honey. Greater antibacterial effects of honeydew honey were observed in inhibiting Staphylococcus aureus and Escherichia coli. In addition, higher bactericidal effects were observed on E. coli that led to morphological alteration and destruction. The combination of this honey with antibiotics also showed synergistic inhibitory effects on E. coli clinical isolates, including antibiotic resistant strains. Lastly, a sugar compound n-butyl β-D-glucopyranoside (C10H20O6) was isolated and characterized from butanolic honeydew honey extract. Although this is the first report about the identification of butyl-glucoside in honey samples, the presence of this compound is most probably an artifact from the extraction process.